Tryptophan 2,3-Dioxygenase Expression Identified in Murine Decidual Stromal Cells Is Not Essential for Feto-Maternal Tolerance - Hoffmann, Delia; Dvorakova, Tereza; Schramme, Florence; Stroobant, Vincent; Van den Eynde, Benoit J. (Frontiers in Immunology, 2020)
Indoleamine 2,3-dioxygenase 1 (IDO1) and tryptophan 2,3-dioxygenase (TDO) catalyze the rate-limiting step of tryptophan catabolism along the kynurenine pathway, which has important immunosuppressive properties, particularly in tumor cells and dendritic cells. The prominent expression of IDO1 in the placenta also suggested a role in preventing immune rejection of fetal tissues, and pharmacological inhibition of IDO1 induced abortion of allogeneic fetuses in mice. However, this was later challenged by the lack of rejection of allogeneic fetuses in IDO1-KO mice, suggesting that other mechanisms may compensate for IDO1 deficiency. Here we investigated whether TDO could contribute to feto-maternal tolerance and compensate for IDO1 deficiency in IDO1-KO mice. Expression of TDO mRNA was previously detected in placental tissues. We developed a new chimeric rabbit anti-TDO antibody to confirm TDO expression at the protein level and identify the positive cell type by immunohistochemistry in murine placenta. We observed massive TDO expression in decidual stromal cells, starting at day E3.5, peaking around E6.5 and E7.5, then declining rapidly while remaining detectable until gestation end. IDO1 was also induced in decidual stromal cells, but only at a later stage of gestation when TDO expression declined. To determine whether TDO contributed to feto-maternal tolerance, we mated TDO-KO and double IDO1-TDO-KO females with allogeneic males. However, we did not observe reduced fertility. These results suggest that, despite its expression in decidual stromal cells, TDO is not a dominant mechanism of feto-maternal tolerance able to compensate for the absence of IDO1. Redundant additional mechanisms of immunosuppression likely take over in these KO mice. The massive expression of TDO during decidualization might suggest a role of TDO in angiogenesis or vessel tonicity, as previously described for IDO1.